Are wetland threats synonymous with environmental problems? analysis of threats to coastal and inland wetlands environment in Nigeria (2014)
Wetlands are a component of the environment and threats facing wetlands might just be a miniature of the larger environmental problems in their immediate vicinity. This paper posited that there is a strong linkage between the major environmental problems in the immediate vicinity of wetlands and threats faced by wetlands. Two questions addressed are (a) are threats faced by coastal wetland substantially different from those faced by inland wetlands, and (b) are wetlands threats synonymous with environmental problems in their immediate vicinity? Questionnaire focusing on the identification of threats to coastal and inland wetlands as well as the environmental problem in their immediate vicinity were administered to wetland users. Results show that the identified threats in both coastal and inland wetlands aye almost similar, and that there is no difference between the identified threats to wetlands and environmental problems recognised by the people. Hence, threats to wetlands might be an extension of the general environmental problems in their immediate vicinity. The results of this study provide basic information that is requiredfor developing measures toward a sustainable management and conservation of the inland and coastal wetlands, and addressing environmental problems in the immediate vicinity of wetlands mayfurther assist in resolving some of the threatsfaced by wetlands.